2018
DOI: 10.3390/cells7120230
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing Phosphatidylcholine on the Surface of the Lipid Droplet Correlates with Altered Protein Binding and Steatosis

Abstract: Alcoholic fatty liver disease (AFLD) is characterized by an abnormal accumulation of lipid droplets (LDs) in the liver. Here, we explore the composition of hepatic LDs in a rat model of AFLD. Five to seven weeks of alcohol consumption led to significant increases in hepatic triglyceride mass, along with increases in LD number and size. Additionally, hepatic LDs from rats with early alcoholic liver injury show a decreased ratio of surface phosphatidylcholine (PC) to phosphatidylethanolamine (PE). This occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 68 publications
5
39
0
Order By: Relevance
“…DZA’s effects occurred largely by (1) increasing TG biosynthesis, (2) decreasing TG lipolysis, and (3) enhancing LD fusion events, thereby expanding the volume of existing LDs. We previously reported that alcohol-induced increases in liver TG and the accumulation of LDs are associated with methylation defects caused by higher levels of intracellular SAH and a lower SAM:SAH ratio [ 1 , 2 , 12 , 13 , 14 ]. We have also shown that treatment with betaine, which blocks the ethanol-induced rise in intracellular SAH and normalizes the reduced SAM:SAH ratio, prevents steatosis and LD accumulation [ 1 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DZA’s effects occurred largely by (1) increasing TG biosynthesis, (2) decreasing TG lipolysis, and (3) enhancing LD fusion events, thereby expanding the volume of existing LDs. We previously reported that alcohol-induced increases in liver TG and the accumulation of LDs are associated with methylation defects caused by higher levels of intracellular SAH and a lower SAM:SAH ratio [ 1 , 2 , 12 , 13 , 14 ]. We have also shown that treatment with betaine, which blocks the ethanol-induced rise in intracellular SAH and normalizes the reduced SAM:SAH ratio, prevents steatosis and LD accumulation [ 1 , 12 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The earliest manifestation of alcohol-induced liver injury is steatosis, characterized by fat accumulation in this organ, which, histologically, is seen as higher numbers and larger sizes of specialized organelles called lipid droplets (LDs) in the cytoplasm of the hepatocyte [ 1 , 2 ]. LDs are the main storage depots for intracellular lipids [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, lipid analysis in these mice revealed that phosphatidylethanolamine (PE) to phosphatidylcholine (PC) conversion mediated by the enzyme phosphatidylethanolamine N-methyltransferase (PEMT) was affected [ 71 ]. Higher PE/PC ratios on LDs are associated with liver injury in rats [ 73 ]. More recently, the specific role of Plin2 in hepatocytes was studied in more detail by comparing full-body and liver-specific Plin2 deletion.…”
Section: Lipid Accumulation In Hepatocytesmentioning
confidence: 99%